Sedimentation Rate and Characteristics of Musi River Mud, Palembang City, South Sumatra - Probowati Sulistiyani; Momon Sodik Imanudin; M Said (Center for Journal Management and Publication, 2019)
The existence of the Musi River is very important not only for the population of South Sumatra, but also for the Bengkulu and Lampung regions. The main problem is the high rate of sedimentation, and the alleged increase in heavy metal content. The research aims were to determine the sedimentation rate and metal content in river mud in dry season. Samples of water, mud, and sediments were taken in the waters of Musi Hilir in the area around Kemarau Island in August-September 2018. The results of laboratory analysis showed that the river had been moderately polluted, where the ammonia content in the water was above the quality standard, and the Fe content in the mud is classified as high (above the quality standard). The sediment accumulation in the nine samples at three stations showed at Station 1 was 0.022429739 g cm-1 day-1. The highest accumulation rate of sediment weight was found at Station 2 which was 0.038456224 g cm-1 day-1. The lowest sediment accumulation rate was found at Station 3, which was only 0.007109631 g cm-1 day-1. The cause of the low accumulation of sediment at Station 3 wasÂ due to flow velocity at this location tends to be large, so that the sediment was difficult to settle. If the assumption was four months dry season, the accumulation of sediment was estimated at 26.9 tons / m2 / 4 months.